Health Status and Quality of Life of Long-term Survivors of Childhood Acute Leukemia: The Impact of Central Nervous System Irradiation. Issue 2 (March 2015) - Benadiba, Joy; Michel, Gérard; Auquier, Pascal; Chastagner, Pascal; Kanold, Justyna; Poirée, Marilyne; Plantaz, Dominique; Padovani, Laetitia; Berbis, Julie; Barlogis, Vincent; Contet, Audrey; Chambost, Hervé; et al.
Abstract : We evaluated the impact of central nervous system irradiation (CNSI) on long-term health status and quality of life (QoL) of childhood lymphoblastic leukemia survivors included in the French L.E.A. (Childhood and Adolescent Leukemia) multicentric cohort. QoL was self-reported in adults and assessed by parents in children and adolescents, using adapted questionnaires. From 2004 to 2009, 630 nongrafted patients were assessed after 11.8±6.3 years from diagnosis. Patients receiving CNSI (18.6%) or chemotherapy alone (81.4%) were compared. The risk of having long-term physical effects was increased with CNSI (odds ratio=3.3; 95% confidence interval, 1.8-5.9), especially regarding growth failure, second tumor, cataract, and overweight. QoL did not differ significantly according to the treatment received, despite a tendency toward lower scores with CNSI in children and adolescents (summary score 63.6±13.3 vs. 71.7±12.4, P =0.14). Compared with French norms, adult survivors had an impaired QoL, especially in mental domains (mental composite score 45.2±9.8 vs. 47.9±2.1, P <0.001). In pediatric survivors, QoL was not impaired and even tended to be higher than population norms (summary score 71.7±12.4 vs. 70.0±4.2, P =0.054), mainly in social and relational domains. In conclusion, QoL seems to be impaired by the trauma of a life-threatening illness in childhood, as well as by the treatment received.